Setup development for spectral response measurement on multijunction solar cells - Socolovsky, Hernán Pablo; Garcia, Javier Andrés; Plá, Juan Carlos (25th European Photovoltaic Solar Energy Conference and Exhibition /5th World Conference on Photovoltaic Energy Conversion, 6-10 September 2010, Valencia, Spain, 2010)
Fil: Garcia, Javier Andrés. Comisión Nacional de Energía Atómica. Departamento de Energía Solar; Argentina